Heme binding of transmembrane signaling proteins undergoing regulated intramembrane proteolysis - Kupke, Thomas; Klare, Johann P.; Brügger, Britta (Communications biology, 2020)
Transmembrane signaling proteins play a crucial role in the transduction of information across cell membranes. One function of regulated intramembrane proteolysis (RIP) is the release of signaling factors from transmembrane proteins. To study the role of transmembrane domains (TMDs) in modulating structure and activity of released signaling factors, we purified heterologously expressed human transmembrane proteins and their proteolytic processing products from Escherichia coli. Here we show that CD74 and TNF alpha are heme binding proteins. Heme coordination depends on both a cysteine residue proximal to the membrane and on the oligomerization of the TMD. Furthermore, we show that the various processing products have different modes of heme coordination. We suggest that RIP changes the mode of heme binding of these proteins and generates heme binding peptides with yet unexplored functions. The identification of a RIP modulated cofactor binding of transmembrane signaling proteins sheds new light on the regulation of cell signaling pathways. Kupke et al. study regulated intramembrane proteolysis (RIP) using recombinant transmembrane proteins CD74 and TNF alpha and find they are heme binding proteins that change their mode of heme binding after proteolytic processing. These data suggest that RIP of type II transmembrane proteins can generate intracellular heme sensor peptides.
Gesehen am 06.04.2020